2017
DOI: 10.1016/j.joto.2017.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Histone deacetylases in hearing loss: Current perspectives for therapy

Abstract: Hearing loss is one of the most frequent health issues in industrialized countries. The pathogenesis and molecular mechanisms of hearing loss are still unclear. Histone deacetylases (HDACs) are emerging as key enzymes in many physiological processes, including chromatin remodeling, regulation of transcription, DNA repair, metabolism, genome stability and protein secretion. Recent studies indicated that HDACs are associated with the development and progression of hearing loss. Dysfunction of HDACs could promote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 96 publications
(125 reference statements)
0
7
0
Order By: Relevance
“…Furthermore, SIRT inhibitor administration activates the proapoptotic protein, an upstream mediator of mitochondrial membrane disruption, through the overexpression of antiapoptotic Bcl-2, which is known to be downregulated by SIRT expression [ 23 , 24 ]. Previous studies have indicated that modifications to the histone proteins are associated with the tumorigenesis of endometrial cancer development [ 25 , 26 , 27 ]. However, a dual function of SIRT1 in tumor promotion and suppression has been described in different cancer types [ 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, SIRT inhibitor administration activates the proapoptotic protein, an upstream mediator of mitochondrial membrane disruption, through the overexpression of antiapoptotic Bcl-2, which is known to be downregulated by SIRT expression [ 23 , 24 ]. Previous studies have indicated that modifications to the histone proteins are associated with the tumorigenesis of endometrial cancer development [ 25 , 26 , 27 ]. However, a dual function of SIRT1 in tumor promotion and suppression has been described in different cancer types [ 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…activates the proapoptotic protein, an upstream mediator of mitochondrial membrane disruption, through overexpression of antiapoptotic Bcl-2, which is known to be down-regulated by SIRT expression [23,24]. Previous studies indicated that modifications in histone proteins are associated with the tumorigenesis of endometrial cancer development [25][26][27]. However, a dual function of SIRT1 in tumor promotion and suppression has been described in different cancer types [28,29].…”
Section: Mhy2256 Induces Autophagic Cell Deathmentioning
confidence: 99%
“…NF-κB is a transcription factor that regulates the expression of a variety of genes involved in inflammation and immunity. 81 , 104 , 105 Sodium butyrate is a well-documented HDAC inhibitor 18 , 27 , 54 , 101 , 105 that has demonstrated anti-inflammatory NF-κB inhibition properties. 50 , 101–105 Butyrate mediates NF-κB activation by rescuing the redox machinery and controlling reactive oxygen species 105 that are highly injurious to hair cells 18 , 132 by suppressing the NF-κB signaling pathways.…”
Section: α-Lipoic Acid L -Carnitine and Butyratementioning
confidence: 99%
“… 10 Irreversible hearing loss can also be the product of disease 12 , 16 , 23 , 24 and is often an unfortunate side effect of the aminoglycoside antibiotics 25–30 and platin-based anticancer drugs. 10 , 27 , 28 , 30–36 Regrettably, once damage has occurred, hearing aids and cochlear implantation are the only compensatory options presently available for affected individuals. 37 …”
Section: Introductionmentioning
confidence: 99%